A two-stage preventive maintenance optimization model incorporating two-dimensional extended warranty. (November 2016) - Su, Chun; Wang, Xiaolin
Abstract: In practice, customers can decide whether to buy an extended warranty or not, at the time of item sale or at the end of the basic warranty. In this paper, by taking into account the moments of customers purchasing two-dimensional extended warranty, the optimization of imperfect preventive maintenance for repairable items is investigated from the manufacturer's perspective. A two-dimensional preventive maintenance strategy is proposed, under which the item is preventively maintained according to a specified age interval or usage interval, whichever occurs first. It is highlighted that when the extended warranty is purchased upon the expiration of the basic warranty, the manufacturer faces a two-stage preventive maintenance optimization problem. Moreover, in the second stage, the possibility of reducing the servicing cost over the extended warranty period is explored by classifying customers on the basis of their usage rates and then providing them with customized preventive maintenance programs. Numerical examples show that offering customized preventive maintenance programs can reduce the manufacturer's warranty cost, while a larger saving in warranty cost comes from encouraging customers to buy the extended warranty at the time of item sale. Highlights: A two-dimensional PM strategy is investigated. Imperfect PM strategy is optimized by considering both two-dimensional BW and EW. Customers are categorized based on their usage rates throughout the BW period. Servicing cost of the EW is reduced by offering customized PM programs. Customers buying the EW at the time of sale is preferred for the manufacturer.